What makes a nursing home a home? Insights from family members and friends. Issue 4 (18th December 2017) - Weeks, Lori; Chamberlain, Stephanie; Keefe, Janice
Abstract : Purpose: The purpose of this paper is to explore the concept of homelikeness from the perspective of family members and friends of nursing home residents across different models of nursing homes. Design/methodology/approach: This mixed-methods study examined survey data collected from 397 family members and friends of residents living in 23 nursing homes representing three models of care (traditional, new augmented, and full scope). Participants completed a homelikeness scale and a measure of the importance of nursing home spaces to family members and friends. This study also involved conducting three focus groups with 20 family members and friends to provide further insights into the findings. Findings: Analysis of survey data indicated quite high levels of homelikeness overall. Significant differences did emerge between traditional model nursing homes compared to new full-scope and new augmented models for all items in the homelikeness scale and for many items about nursing home spaces. Qualitative results provided insights into how homelikeness can be fostered through public and private spaces and through care and relationships. Research limitations/implications: As this study was conducted in one Canadian province, the results may not be applicable to other geographic areas. In addition, there are limitations in survey response rate. Practical implications: Homelikeness can be supported across models of care by fostering relationships between residents and staff, ensuring that that family and friends feel welcome, and creating public and private physical spaces that are conducive to new and ongoing relationships. Originality/value: The results provide evidence to nursing home decision makers about how to foster a homelike environment in various models of nursing homes.